2015
DOI: 10.3389/fgene.2015.00014
|View full text |Cite
|
Sign up to set email alerts
|

Toxicogenomics profiling of bone marrow from rats treated with topotecan in combination with oxaliplatin: a mechanistic strategy to inform combination toxicity

Abstract: Combinations of anticancer agents may have synergistic anti-tumor effects, but enhanced hematological toxicity often limit their clinical use. We examined whether “microarray profiles” could be used to compare early molecular responses following a single dose of agents administered individually with that of the agents administered in a combination. We compared the mRNA responses within bone marrow of Sprague-Dawley rats after a single 30 min treatment with topotecan at 4.7 mg/kg or oxaliplatin at 15 mg/kg alon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 53 publications
1
8
0
Order By: Relevance
“…We have identified several genes belonging to the p53 signaling pathway, DNA replication, and positive regulators of apoptotic process that were differentially expressed by TPT treatment. Using microarray differential gene expression analysis, Davis et al (2015) have reported that topotecan exposure in rat bone marrow resulted in enrichment of cell cycle and DNA replication pathways similar to our observations in this study. It should be noted that the relationship between chromatin remodeling, cell cycle and DNA repair factors are usually not discussed in relation to DNA damage response mechanisms following topotecan exposure.…”
Section: Discussionsupporting
confidence: 88%
“…We have identified several genes belonging to the p53 signaling pathway, DNA replication, and positive regulators of apoptotic process that were differentially expressed by TPT treatment. Using microarray differential gene expression analysis, Davis et al (2015) have reported that topotecan exposure in rat bone marrow resulted in enrichment of cell cycle and DNA replication pathways similar to our observations in this study. It should be noted that the relationship between chromatin remodeling, cell cycle and DNA repair factors are usually not discussed in relation to DNA damage response mechanisms following topotecan exposure.…”
Section: Discussionsupporting
confidence: 88%
“…If this hypothesis is true, these patterns can then be used to provide some initial degree of discrimination between drug combinations with higher risk of combination toxicity. Initial evidence of this has been published where we show that the administration of oxaliplatin in combination with topotecan, or either drug alone, in the rat elicits gene expression changes in the bone marrow that are dependent on the order of the administration and indicative of enhance toxicity 1 .…”
Section: Background and Summarymentioning
confidence: 83%
“…RNA samples were converted into labeled target antisense RNA (cRNA) using the Single-Round RNA Amplification and Biotin Labeling System (Enzo Life Sciences, Farmingdale, NY). Microarray analysis was performed as previously described 1 . Briefly, 2.5 μg of total RNA was converted into double stranded cDNA via reverse transcription using an oligo-d(T) primer-adaptor.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Details of the analysis are as previously described [10]. The data are available in the Gene Expression Omnibus (GEO) [11, 12] under accession number GSE63902.…”
Section: Resultsmentioning
confidence: 99%